Enterohemolytic phenotypes and genotypes of shiga toxin-producing Escherichia coli O111 strains from patients with diarrhea and hemolytic-uremic syndrome. - Schmidt, H (1996)
Thirty-six Shiga toxin-producing Escherichia coli (STEC) O111:H- strains, 18 of which were isolated from patients with hemolytic-uremic syndrome (HUS) and 18 from patients suffering from diarrhea, were investigated for their enterohemolytic phenotypes and genotypes. Twenty-two strains were EHEC hemolysin (EHEC Hly) positive by probe hybridization and by PCR with sequences complementary to the EHEC hlyA gene of E. coli O157:H7, but only 20 of these were hemolytic on blood agar plates. The remaining 14 strains were EHEC Hly negative according to DNA-based methods and did not express the enterohemolytic phenotype. The enterohemolytic phenotype was observed in 16 of 18 (88%) strains from patients with HUS but only in 4 of 18 (22.2%) of the STEC O111:H- strains from patients with diarrhea. All STEC O111:H- strains carried large plasmids, as shown by plasmid analysis, but only plasmids of EHEC Hly probe-positive strains hybridized with the CVD419 probe. A BamHI fragment of approximately 12 kb was cloned from the large plasmid of the E. coli O111:H- strain 78/92 and shown to mediate hemolytic activity when transformed into the E. coli laboratory strain HB101. The EHEC O111 hlyA gene was sequenced completely and shown to have 99.4% sequence identity to the corresponding EHEC O157 hlyA gene of the E. coli O157:H7 strain EDL 933. Our results indicate that detection of EHEC Hly either by DNA-based methods or by investigation of the enterohemolytic phenotype on blood agar alone is insufficient for screening STEC O111 strains. However, the high incidence of EHEC Hly in isolates from patients with HUS and its rare occurrence in isolates from patients with diarrhea may indicate that STEC O111 strains have a distinct pathogenic potential for humans and that the presence of EHEC Hly increases the ability of an STEC O111 strain to cause extraintestinal complications in humans.